Climate Risk Country Profile : Philippines - World Bank Group (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
The Philippines is an archipelago comprised of 7,107 islands with a humid climate and a topography characterized by mountainous terrain bordered by narrow coastal plains. Considered one of the most biologically rich and diverse countries in the world, the Philippines also has one of the world’s longest coastlines, and its marine and coastal resources yield in goods and services. The country’s mineral, oil, gas, and geothermal potential are also significant. The Philippines is also considered to be among the world’s most disaster-prone countries. Commonly occurring hazards include floods, droughts, typhoons, landslides and mudslides, earthquakes, and volcanic eruptions. This document aims to succinctly summarize the climate risks faced by the Philippines. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods and economies, many of which are already underway. Climate change is a major risk to good development outcomes, and the World Bank Group is committed to playing an important role in helping countries integrate climate action into their core development agendas. The World Bank Group (WBG) and the Asian Development Bank (ADB) are committed to supporting client countries to invest in and build a low-carbon, climate resilient future, helping them to be better prepared to adapt to current and future climate impacts.